Rural Development Management Strategy In Empowerment In Neglasari Pakenjeng Garut, West Java - Dadang, Asep (Teumulong: Journal of Community Service, 2023)
The goal of national development is to develop Indonesian people as a whole and comprehensively. There are more rural communities in every country, including Indonesia, than urban communities, so they need a development management strategy to manage them. Neglasari Pakenjeng Garut, West Java is one of the rural areas located in a mountainous location, so it requires a development planning arrangement as a form of public service. Based on the results of research using descriptive methodology with the title: "Rural Development Management Strategy for Empowerment in Neglasari Pakenjeng Garut, West Java ", it can result in improvements in the fields of education and the economy.